Contribution of starburst nuclei to the diffuse gamma-ray and neutrino flux. Issue 4 (13th March 2020) - Peretti, Enrico; Blasi, Pasquale; Aharonian, Felix; Morlino, Giovanni; Cristofari, Pierre
ABSTRACT: In nuclei of starburst galaxies (SBGs), the combination of an enhanced rate of supernova explosions and a high gas density suggests that cosmic rays (CRs) can be efficiently produced, and that most of them lose their energy before escaping these regions, resulting in a large flux of secondary products, including neutrinos. Although the flux inferred from an individual starburst region is expected to be well below the sensitivity of current neutrino telescopes, such sources may provide a substantial contribution to the diffuse neutrino flux measured by IceCube. Here, we compute the gamma-ray and neutrino flux due to SBGs based on a physical model of CR transport in a starburst nucleus, and accounting for the redshift evolution of the number density of starburst sources as inferred from recent measurements of the star formation rate. The model accounts for gamma-ray absorption both inside the sources and in the intergalactic medium. The latter process is responsible for electromagnetic cascades, which also contribute to the diffuse gamma-ray background at lower energies. The conditions for acceleration of CR protons up to energies exceeding 10 PeV in starburst regions, necessary for the production of PeV neutrinos, are investigated in a critical way. We show that starburst nuclei can account for the diffuse neutrino flux above 200 TeV, thereby producing 40 per cent of the extragalactic diffuse gamma-ray background. Below 200 TeV, the flux from starburst appears to be somewhat lower than the observed one, where both the Galactic contribution and the flux of atmospheric neutrinos may account for the difference.